2016
DOI: 10.1016/j.alcohol.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ethanol reward sensitivity by nicotinic acetylcholine receptors containing the α6 subunit

Abstract: The prevalent co-abuse of nicotine and alcohol suggests a common neural mechanism underlying the actions of the two drugs. Nicotine, the addictive component of tobacco, activates nicotinic acetylcholine receptors (nAChRs) containing the α6 subunit (α6* nAChRs) in dopaminergic (DAergic) neurons of the ventral tegmental area (VTA), a region known to be crucial for drug reward. Recent evidence suggests that ethanol may potentiate ACh activation of these receptors as well, although whether α6* nAChR expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(53 reference statements)
0
12
1
Order By: Relevance
“…This is vital, as it shows that α6*-nAChRs are involved in the process of dependence and its accompanying behaviors, rather than the many physiological influences, such as ataxia, that ethanol can have on the brain other than addiction. Contrary to our findings, Guildford et al (Guildford et al , 2016) recently reported that α6 KO mice demonstrate an ethanol CPP (2 g/kg IP) that is similar in magnitude to that of WTs. However, at a conditioning dose of 3 g/kg, CPP was absent in α6 KO mice, as was observed with the 2 g/kg dose in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is vital, as it shows that α6*-nAChRs are involved in the process of dependence and its accompanying behaviors, rather than the many physiological influences, such as ataxia, that ethanol can have on the brain other than addiction. Contrary to our findings, Guildford et al (Guildford et al , 2016) recently reported that α6 KO mice demonstrate an ethanol CPP (2 g/kg IP) that is similar in magnitude to that of WTs. However, at a conditioning dose of 3 g/kg, CPP was absent in α6 KO mice, as was observed with the 2 g/kg dose in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Inconsistent results have also been found with studies of genetically modified animals. While animals lacking the α6 subunit do not differ in ethanol consumption (Guildford et al, 2016; Kamens et al, 2012), mice with a hypersensitive α6 subunit consume significantly more ethanol than wildtype animals (Powers et al, 2013). Together, these data suggest that α6β2 nicotinic acetylcholine receptors may be involved in ethanol intake but additional research is needed to clarify their role.…”
Section: Discussionmentioning
confidence: 99%
“…Mice that lack the α6 subunit do not differ in ethanol consumption compared to wildtype animals (Guildford, Sacino, & Tapper, 2016; Kamens et al, 2012), but do differ in sensitivity to the sedative effects of ethanol (Kamens et al, 2012) and sensitivity to ethanol reward at high doses (Guildford et al, 2016). In contrast, transgenic mice that exhibit a hypersensitive α6 subunit consumed significantly more ethanol than wildtype animals and displayed ethanol reward at low doses (Powers et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The α4 nAChR subunit is critical for the reduction of alcohol consumption by varenicline, since varenicline does not reduce alcohol consumption in α4 KO mice (Hendrickson et al, 2010). Additionally, the α6 nAChR subunit is critical in mediating the rewarding effects of alcohol, as α6 KO mice have reduced alcohol-induced dopaminergic activation (Liu et al, 2013) and reduced expression of alcohol CPP (Guildford et al, 2016). Mice with a hypersensitive α6 nAChR knock-in subunit consume more alcohol than their wild-type counterparts (Powers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%